PENGARUH OPINI AUDIT, TEMUAN AUDIT, DAN KERUGIAN DAERAH TERHADAP TINGKAT KORUPSI DI JAWA TENGAH - Amalia Rahmah Pertiwi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2022)
This study aims to provide additional empirical evidence on the effect of audit opinion, audit findings and regional losses regional losses due to corruption in Central Java. Hypothesis testing was carried out using multiple linear regression analysis. The data collection method used purposive sampling method sourced from BPK related to IHPS and LHP LKPD, BPS related to the realization of local government expenditures, and the High Court related to data on prosecution of criminal acts of corruption The results obtained in this study indicate that audit opinions, audit findings, and regional losses have no effect on the level of corruption in both districts and cities in Central Java Province.